EVALUATION OF MOBILE APPLICATIONS RELATED TO THE NURSING PROCESS - Azevedo, Isabela Flávia Feitosa; Chaves, Arlane Silva Carvalho [UNESP]; de Jesus, Layane Mota de Souza [UNESP]; Jensen, Rodrigo (FapUNIFESP (SciELO), 2024)
Objective: to evaluate the quality of applications related to the Nursing Process available on Google Play using the Mobile App Rating Scale (MARS). Methods: a descriptive study, designed as an evaluation of mobile applications, in order to identify and evaluate applications related to the nursing process, available on the Android platform. The search was conducted on the Google Play store from September to October 2021. The Mobile App Rating Scale (MARS) was used to assess the quality of apps in the domains of engagement, functionality, aesthetics and information quality, and their respective items, on a five-point scale. The quality assessment was carried out by the authors of the study. Results: a total of 53 applications related to the Nursing Process were identified, which were free and predominantly available in English (64%). The apps obtained an overall mean quality rating in the domains of engagement (3.1), functionality (4.8), aesthetics (4.6) and information quality (4.26). Conclusion: the apps evaluated were of good quality overall. Engagement was identified as an aspect to be improved in the Nursing Process apps.
EVALUACIÓN DE APLICACIONES MÓVILES RELACIONADAS AL PROCESO DE ENFERMERÍA
AVALIAÇÃO DE APLICATIVOS MÓVEIS RELACIONADOS AO PROCESSO DE ENFERMAGEM
Keywords: Educational technology; Mobile apps; Nursing informatics; Nursing process